2016
DOI: 10.31073/agrovisnyk201604-11
|View full text |Cite
|
Sign up to set email alerts
|

Protected lipids and fatty acids in rations of feeding of cattle

Abstract: The purpose. To analyze results of domestic and foreign scientific probes of last years as to productive and metabolic influence, increase of productivity of fatty additives in rations of feeding of different age and productive groups of cattle. Methods. Analytical, theoretical generalization. Results. Results of own probes, domestic and foreign authors carried out in last years concerning metabolic and productive action of protected lipids and fatty acids at use of their additives in rations of feeding of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They suggested that rumen-inert dry fats are used to avoid interference with rumen function that in turn could decrease nutrients supplied by the rest of the ration ingredients. It is known that application of fat supplements in a diet of cattle increases their caloric content and makes positive impact on milk productivity, feed payment as well as growth and development of animals [VOVK et al, 2006] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that rumen-inert dry fats are used to avoid interference with rumen function that in turn could decrease nutrients supplied by the rest of the ration ingredients. It is known that application of fat supplements in a diet of cattle increases their caloric content and makes positive impact on milk productivity, feed payment as well as growth and development of animals [VOVK et al, 2006] .…”
Section: Resultsmentioning
confidence: 99%
“…Such products are easily handled and are more inert in the rumen than native fats. The unsaturated fatty acids in calcium soap products are only partially protected [VOVK et al, 2006] .…”
Section: Introductionmentioning
confidence: 99%